Protectant activity of reduced concentration copper sprays against Alternaria brown spot on 'Fortune' mandarin fruit in Spain - Vicent, Antonio; Armengol, Josep; García-Jiménez, José (2017)
Alternaria brown spot (ABS) of mandarins is a serious disease of fruit and foliage of citrus, causing defoliation, fruit drop and rind blemishes on susceptible cultivars. In Spain, the disease causes severe losses on the late-maturing cultivars for export of 'Fortune' and 'Nova'. Several fungicide sprays are needed to protect susceptible organs during the critical infection periods through the growing season. In Spain, copper compounds and mancozeb are the only fungicides registered for ABS control in conventional production, and copper is accepted for organic production as long as total dose does not exceed 6 kg ha(-1) annually, but considerably higher amounts are currently applied for ABS control. Therefore, experiments were performed to evaluate the protective effect of reduced copper concentrations on fruits of the highly susceptible cultivar 'Fortune'. All copper compounds evaluated effectively protected 'Fortune' fruit from infection for the 28-d period of study in two field trials, where a daily average of 9 h of leaf wetness was recorded. Reducing the concentration of copper in the spray tank from 1 to 0.5 gl(-1) had no negative effect on persistence. Copper compounds applied at 0.5 gl(-1) displayed excellent rain fastness in the simulated rainfall experiment, even with the highest precipitation of 90 mm. The use of reduced concentration copper sprays would diminish the economic and environmental costs of disease control and may assist growers moving towards organic production. (C) 2008 Elsevier Ltd. All rights reserved.